2016
DOI: 10.1016/j.rchipe.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Gastrosquisis: ¿una pandemia con tasas en aumento? Experiencia del estudio colaborativo latino americano de malformaciones congénitas (ECLAMC) en Chile. Período 1982-2014

Abstract: There has been a significant increase in the gastroschisis prevalence at birth in Chile from 1995, and this anomaly is associated with a low maternal age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…The association between young maternal age and gastroschisis is a well–documented risk factor 1416,19,20 . However, the increase in gastroschisis prevalence is not because of an increase in teen births, since birth rates have decreased among mothers <25 years, and the highest increase in prevalence trend occurred among mothers aged 30–34 years.…”
Section: Discussionmentioning
confidence: 99%
“…The association between young maternal age and gastroschisis is a well–documented risk factor 1416,19,20 . However, the increase in gastroschisis prevalence is not because of an increase in teen births, since birth rates have decreased among mothers <25 years, and the highest increase in prevalence trend occurred among mothers aged 30–34 years.…”
Section: Discussionmentioning
confidence: 99%
“…The adjudged reason for such an increase in the prevalence could not be substantiated. A few authors suggested increasing prenatal ultrasound use, which makes the clinician be able to pick up the at-risk fetus very early [29,30]. Meanwhile, a few cases were seen in Southern America, covering Honduras, Chile, Brazil, and then Australia, etc.…”
Section: Epidemiologymentioning
confidence: 99%
“…Meanwhile, a few cases were seen in Southern America, covering Honduras, Chile, Brazil, and then Australia, etc. [29,30]. One literature reported that there had been an estimated 300% increase in the incidence of GS from 1994 up till 2015, otherwise regarded as a "Gastroschisis pandemic which is strongly related to low maternal age that is maternal age <20 years" [29,30].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several communications have reported a significant increase in the prevalence of gastroschisis at birth in the last three decades. It is referred to as "a pandemic strongly associated to low maternal age" in many countries [4]. In gastroschisis, unlike omphalocele, there is no membranous covering over the intestine, which is markedly edematous and erythematous and is often enclosed in a fibrin mat.…”
Section: м а макароваmentioning
confidence: 99%